A bivalent, bispecific Dab-Fc antibody molecule for dual targeting of HER2 and HER3. Issue 1 (1st January 2021) - Rau, Alexander; Kocher, Katharina; Rommel, Mirjam; Kühl, Lennart; Albrecht, Maximilian; Gotthard, Hannes; Aschmoneit, Nadine; Noll, Bettina; Olayioye, Monilola A.; Kontermann, Roland E.; Seifert, Oliver
ABSTRACT: Dual targeting of surface receptors with bispecific antibodies is attracting increasing interest in cancer therapy. Here, we present a novel bivalent and bispecific antagonistic molecule (Dab-Fc) targeting human epidermal growth factors 2 and 3 (HER2 and HER3) derived from the Db-Ig platform, which was developed for the generation of multivalent and multispecific antibody molecules. Dab-Fc comprises the variable domains of the anti-HER2 antibody trastuzumab and the anti-HER3 antibody 3–43 assembled into a diabody-like structure stabilized by CH 1 and CL domains and further fused to a human γ1 Fc region. The resulting Dab-Fc 2 × 3 molecule retained unhindered binding to both antigens and was able to bind both antigens sequentially. In cellular experiments, the Dab-Fc 2 × 3 molecule strongly bound to different tumor cell lines expressing HER2 and HER3 and was efficiently internalized. This was associated with potent inhibition of the proliferation and migration of these tumor cell lines. Furthermore, IgG-like pharmacokinetics and anti-tumoral activity were demonstrated in a xenograft tumor model of the gastric cancer cell-line NCI-N87. These results illustrate the suitability of our versatile Db-Ig platform technology for the generation of bivalent bispecific molecules, which has been successfully used here for the dual targeting of HER2 and HER3.